The Influence of Transparency and Accountability on Parental Trust and Its Impact on Parental Loyalty of Students of Shidqia Islamic School Jatisari Middle School, Jatiasih, Bekasi City - Muhammad Taufik; Heru Mulyanto (Journal GoodWill, 2025)
Education is an important element in developing quality human resources. In the formal education system, schools not only function as a place of learning but also as an institution that builds collaboration between students, teachers, and parents. The success of an educational institution is not only determined by the academic achievements of students, but also by the harmonious relationship between the institution and its stakeholders, especially parents. Parents' trust and loyalty to educational institutions are important keys in creating productive relationships and supporting the sustainability and development of schools. This study aims to analyze the effect of openness and accountability on parental trust and its impact on parental loyalty. This study was conducted at SMP Shidqia Islamic School, located at Jl. Suryadharma No. 1A, Aerospace Earth Permai Housing, Jatisari , Jatiasih , Bekasi City. The approach used in this study was quantitative, with a data collection method through distributing questionnaires to 87 parents using a simple random sampling technique. The data obtained were analyzed using descriptive statistical techniques to provide an overview of the research variables, as well as the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) approach. Data analysis was conducted using SmartPLS software with three main stages, namely evaluation of the measurement model (outer model), evaluation of the structural model (inner model), and hypothesis testing to identify direct and indirect influences, including the role of mediating variables. The results of this study indicate that openness and accountability each have a positive and significant effect on the trust and loyalty of parents of students. In addition, parental trust also has a positive and significant effect on the loyalty of parents of students. However, the variable of parental trust does not act as a mediator in the relationship between openness and accountability on the loyalty of parents of students at SMP Shidqia Islamic School. Overall, the independent variables in this study are able to explain the dependent variable by 68.2%.